The Mediating Role of Strategic Planning in Strengthening the Relationship Between Organizational Justice and Organizational Development: An Applied Study in the Baghdad/Al-Rusafa Health Department - Hani Reda, Saif; Fawaz Masoud , Mazen (Journal of Economics and Administrative Sciences, 2024)
The purpose of this study is to evaluate the impact of organizational justice on organizational development using strategic planning as a mediating variable. Therefore, the main question for the problem of the current study is whether organizational justice is of great importance and can enhance organizational development strategically. As a case study, an applied descriptive and analytical study was conducted on the Rusafa Health Department in Baghdad. The study included 182 individuals in the administrative levels of the Baghdad Al-Rusafa Health Department. Questionnaires were used as a main tool for collecting and analyzing data using (SPSS (to achieve the objectives and test hypotheses of the study. This study confirms that applying Justice Theory to organizations through organizational justice topics is a basic condition for organizational development. These practices maintain the organization’s reputation and thus employee retention. The results indicated that organizational justice has a significant impact on organizational development in its various dimensions through strategic planning among workers in the Rusafa Health Department.